2022
DOI: 10.7189/jogh.12.04061
|View full text |Cite
|
Sign up to set email alerts
|

10-year opportunistic mammographic screening scenario in Brazil and its impact on breast cancer early detection: a nationwide population-based study

Abstract: Background Mammographic screening has been used to reduce breast cancer mortality worldwide and remains the main modality for the early detection of this disease. Women from low- and middle-income countries still lack access to periodic mammograms and efficient health care. This cross-sectional study aimed to explore opportunistic mammographic coverage in Brazil, while considering the privately insured population and its association with early breast cancer (EBC) detection. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…A recent study from Brazil found a nationwide prevalence of stage 0 (in situ) or stage I breast cancer of 31% among women aged 50 to 70 years and a prevalence of 36% in the state of São Paulo. 12 In our study based in Campinas, a municipality of the state of São Paulo, tumors staged 0 (in situ) or I accounted for 40% of women aged 50 to 59 years and 44% of women aged 60 to 69 years. There are 2 possible explanations for this higher prevalence.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…A recent study from Brazil found a nationwide prevalence of stage 0 (in situ) or stage I breast cancer of 31% among women aged 50 to 70 years and a prevalence of 36% in the state of São Paulo. 12 In our study based in Campinas, a municipality of the state of São Paulo, tumors staged 0 (in situ) or I accounted for 40% of women aged 50 to 59 years and 44% of women aged 60 to 69 years. There are 2 possible explanations for this higher prevalence.…”
Section: Discussionmentioning
confidence: 65%
“…Stage was registered according to the American Joint Committee on Cancer. 12 The study's end for censorship was March 31, 2020, which was the first month of the isolation period in Brazil because of the COVID-19 pandemic. The MIS in Campinas is very accurate and gets updated periodically with the MIS of surrounding cities, a well-established linkage in the region.…”
Section: Methodsmentioning
confidence: 99%
“…Organized screening programs can contribute to improved coverage, reduced mortality, and reduced health disparities 11,14,22 . Latin American selected countries in this study do not comply with the key performance indicators defined for organized screening programs.…”
Section: Discussionmentioning
confidence: 99%
“…Peisl S et al (2019) compared a group of 989 women in Switzerland that received opportunistic or organized screening and observed that women in the organized program presented more frequently with in situ rather than invasive cancer and were less likely to undergo radiation therapy 11 . On the other hand, the existence of an opportunistic screening program in Brazil for the last 10 years has maintained screening rates at about 30% with significantly lower rates and early-stage diagnosis in underserved populations 22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in Brazil, mammographic screening has been an opportunistic procedure. Despite educational campaigns, mammography coverage is currently around 35% of the target population, well below the 70% recommended worldwide 15 .…”
Section: Barriers To Disease Control and Strategies To Overcome Itmentioning
confidence: 93%